Konstruksi Predominant Leader dalam Kebijakan Moon Jae In terhadap Jepang dalam isu Comfort Women pada Tahun 2017-2022 - Candelaria, Arizki Putri (Department of International Relations, University of Mataram, 2023)
Comfort Women refers to the practice of forced sexual services on thousands of women by Japanese soldiers during World War II. This issue has been a source of tension in relations between South Korea and Japan for several years. In this research, the concept of